Evaluation of a hydrophobic gel adhering to the gingiva in comparison with a standard water‐soluble 1% chlorhexidine gel after scaling and root planing in patients with moderate chronic periodontitis. A randomized clinical trial. Issue 1 (5th June 2015) - Rusu, D; Stratul, S‐I; Sarbu, C; Roman, A; Anghel, A; Didilescu, A; Jentsch, H
Abstract: Objectives: To evaluate the clinical, microbiological and enzymatic activity of a hydrophobic chlorhexidine‐based gingiva‐adhering gel containing herbal ingredients, compared with a commercially available 1% chlorhexidine water‐soluble gel, during non‐surgical therapy of moderate chronic periodontitis. Methods: A total of 34 subjects participated in this 6‐month blinded randomized parallel controlled trial (ISRCTN35210084). After scaling and root planing (SRP), test group received the gel, by rubbing on the gingiva, once every second day, for 14 days. The control group received the control gel twice daily. Clinical parameters considered were the approximal plaque index, simplified oral hygiene index, modified gingival index, bleeding on probing, probing depth and clinical attachment level (primary outcome), assessed at baseline, 3 and 6 months, together with the frequency of detection of Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis ( P.g .), Prevotella intermedia, Treponema denticola ( T.d .), Tannerella forsythia ( T.f .), and activity of neutrophil elastase and myeloperoxidase (secondary outcomes). Results: At 3 and 6 months, all clinical parameters improved significantly, without significant intergroup differences, except OHI‐S, which improved at 3 months ( P < 0.05). Microbiological data resulted in no significant intergroup differences at baseline and 6 months. At 3 months, significant differences for P.g ., T.f . and T.d . were noted. A significant reduction of neutrophil elastase after 3 and 6 months was observed ( P < 0.005), without significant intergroup differences. For myeloperoxidase, significant reductions were noted in both groups ( P < 0.005 and P < 0.05), but no significant intergroup differences. The tested product seemed to have an increased efficacy, due to longer persistence on the gingiva, with reduced application frequency. Conclusions: Both products had a relatively similar influence on the clinical, microbiological and enzymatic outcomes at 3 and 6 months after SRP.